Improvement of clinical outcomes in dialysis: No convincing superiority in dialysis efficacy using hemodiafiltration vs high‐flux hemodialysis. Issue 4 (14th April 2020) - Abdelsalam, Mostafa; Demerdash, Tarek M.; Assem, Mohammed; Awais, Muhammad; Shaheen, Mahmoud; Sabri, Ayman; Alanany, Hany; Kashgary, Abdullah; Alsuwaida, Abdulkareem
Abstract: Hemodiafiltration (HDF) is not associated with lower mortality risk compared to standard hemodialysis (HD). However, there are many critical clinical outcomes in dialysis patients in addition to mortality; the impact of HDF on these other outcomes is not clear. This retrospective study included all patients referred to DaVita Clinics in the Kingdom of Saudi Arabia. High‐flux HD was the initial modality in all patients. Those who did not achieve adequacy targets or those with poorly controlled phosphorus were switched to postdilution HDF using 18 to 23 L exchange per treatment. Patients dialyzing with a central venous catheter, patients who dialyzed less than 90 days at DaVita, and those with interrupted HDF were excluded. Of the 1115 patients, 215 (19%) were on HDF and 900 on high‐flux HD; the median follow‐up was 6 months for all patients. The HDF group showed a significant reduction in serum phosphate ( P  < .001), a significant increase in serum calcium ( P  < .012) and a significant improvement in Kt/V ( P  < .0001). The HDF group had significantly higher hemoglobin levels than the HD group ( P  = .024), with a significant reduction in weekly erythropoiesis‐stimulating agent dose after starting HDF ( P  < .001). A modified protocol that included prolonged dialysis duration, larger‐sized dialyzer, faster blood flow rates, and adding hemofiltration fluid may be helpful in achieving the recommended targets. Thus, HDF can enable the achievement of adequate dialysis care in some patients. Randomized‐controlled clinical trials are necessary to confirm these findings.